2017
DOI: 10.1002/anie.201703412
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Benign, Rapid, and Selective Extraction of Gold from Ores and Waste Electronic Materials

Abstract: The extraction of gold from ores and electronic waste is an important topic worldwide, as this precious metal has immense value in a variety of fields. However, serious environmental pollution and high energy consumption due to the use of toxic oxidation reagents and harsh reaction conditions is a well-known problem in the gold industry. Herein, we report a new chemical method based on the combined use of N-bromosuccinimide (NBS) and pyridine (Py), which has a greatly decreased environmental impact and reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 36 publications
0
98
0
Order By: Relevance
“…These findings will be beneficial for the development of novel ideas related to CNT-based desalination and purification, such as applying an electric field to push the cations away from the inlets of the CNTs as proposed for the thin CNTs in our previous theoretical study [8]. The high salt accumulation could also be used for the collection/extraction of noble metals by using CNTs in solutions containing trace amounts of noble metal salts for the production/recycling of noble metals [34], environmental conservation [71], and directional transport in biological systems [72]. It should be noted that conventionally, noble metal accumulations [33,73,74] in CNTs have only been observed in high-concentration solutions, and a cation-anion pair have been reported within nanotubes [75].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…These findings will be beneficial for the development of novel ideas related to CNT-based desalination and purification, such as applying an electric field to push the cations away from the inlets of the CNTs as proposed for the thin CNTs in our previous theoretical study [8]. The high salt accumulation could also be used for the collection/extraction of noble metals by using CNTs in solutions containing trace amounts of noble metal salts for the production/recycling of noble metals [34], environmental conservation [71], and directional transport in biological systems [72]. It should be noted that conventionally, noble metal accumulations [33,73,74] in CNTs have only been observed in high-concentration solutions, and a cation-anion pair have been reported within nanotubes [75].…”
mentioning
confidence: 92%
“…This discovery helps explain the recent findings of negligible water flow and ion permeation across wider CNTs in salt solution and opens new avenues for the development of novel ideas related to CNT-based desalination. It also provides a new strategy for the collection of noble metal salts in solutions containing traces of noble metal salts, which has great economic value [34] and significance for environmental conservation. Our theoretical studies reveal that this high salt accumulation of CNTs can be mainly attributed to the strong hydrated cation-π interactions between hydrated cations and π electrons in the aromatic rings of CNTs.…”
mentioning
confidence: 99%
“…Very recently, a new, low-toxicity method for the leaching of gold from WPCBs using a synergistic mixture of N-bromosuccinamide (NBS) as an oxidant and pyridine (py) as a ligand has been described ( Figure 23) [97] Experimental variation of the reagents and conditions showed that gold dissolution was maximised (90%) using 10 mM NBS, 100 mM py, at pH 8.2 and 25 o C, and contrasts to only 77% gold dissolution using KI/I2; the cost of these latter reagents is 20x greater.…”
Section: Chemical Design In Gold Recovery By Urban Miningmentioning
confidence: 99%
“…They are, therefore, precious and their demand is continuously growing. The possibility to recycle the elements from multi‐metal materials such as printed circuit boards (PCBs) is crucial when sustainability and the circular economy are considered . In general, recovery of Au in the mining industry is mostly based on the hydrometallurgical cyanidation process, which relies on the use of stoichiometric amounts of cyanide salts and produces large amounts of hazardous waste .…”
Section: Figurementioning
confidence: 99%